Death from Barotrauma Due to Compressed Air: A Medico‐legal Analysis. Issue 6 (19th September 2016) - Giugliano, Pasquale; Massoni, Francesco; Crisci, Antonello; Ricci, Serafino
Abstract: Lesions of the digestive tract due to barotrauma resulting from compressed air application are not common, are rarely lethal, and largely affect the sigmoid and descending colon. Moreover, their pathogenic mechanism is a topic of discussion because these lesions have multiple characteristics. Here, the authors describe an autoptic case of death from lesions of the ascending and transverse segments, with perforations and bleeding suffusions as well as ischemic areas covered the colonic wall that was extremely thinned, congested, and hemorrhagic, with considerable flattening leading to disappearance of the mucosal folds and with numerous petechial hemorrhages. The pathological framework of lung congestion made it possible to identify the mechanism responsible for this death as depletion of the heart's pumping function, which contributed significantly to the acute respiratory failure due to respiratory distress as well as to reduced mobility of the diaphragm due to intestinal distension. Acute heart failure played an important role in this death.